Metátese de fechamento de anel: espiro-anelação estereosseletiva / Reações multicomponentes de Diels-Alder na síntese de compostos tricíclicos - Pereira, Fabiana Massarente (Universidade Federal de São Carlos, 2011)
In this work, a study of different synthetic ways was made in order to obtain spiro compounds starting from R-(-)-carvone, getting to the formation of cycloheptenone as an intermediate, which undergoes two consecutives alkylations to the formation of a bis alkylated compound which would be submitted to a ring closing metathesis and consequently reaching the spiro compound. The synthesis of the cycloheptenone was started using R-(-)-carvone as starting material through three different routes (Scheme I), obtaining better yields when the third route was used, where the Nozaki reaction is responsible for the ring expansion. Besides that, this route was faster because it has only two steps. Having synthesized cycloheptenone, the first alkylation of this molecule was tested with allyl chloride and potassium terc-butoxide in terc-butanol yielding mono-alkylated product. The second alkylation only yielded the product when the solvent was substituted for dimethylsulfoxide, instead of t-BuOH, using 3-chloro-2- XX methylpropene as alkylating agent. Although the formation of bis-alkylated product was confirmed, the yields were low. Trying to obtain other bis-alkylated products, reactions with 2,3-dichloropropene and 2,3-dibromopropene were tested. Having the bis alkylated product obtained using 3-chloro-2- methylpropene as reagent, the ring closing metathesis (RCM) with first generation Grubbs catalyst 3 was tested. However, after 24 hours, the formation of the desired spiro compound didn t happen under these conditions.
Keywords: Química orgânica; Metátese de fechamento de anel; Diels-Alder; Reações multicomponente; Compostos tricíclicos; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA